KOMPRES JAHE MERA TERHADAP TINGKAT PENURUNAN GOUT ARTHRITIS PADA LANSIA DI WILAYAH KERJA PUSKESMAS TOLANGOHULA KABUPATEN GORONTALO - Rona Febriyona; Inne Ariane Gobel (-, 2021)
Gout arthritis is the desease which attack Joint excess purin in blood that causes pain, swelling and redness in Joints. This research was conducted to identify the effect before and after in giving red ginger compression in decreasing pain level of Gout Arthritis on elderly. Research design used Quasy eksperiment Pre-test post-test with involved control group and treatment control. Population are all of erderly suffered Gout Arthrtis at puskesmas Tolangohula Kabupaten Gorontalo there are 20 respondents. Red ginger compression done 2 times a day on pain Joints, red ginger compression assessment before and after treatment which used independent T-test on significance level 95 % (a=0,05). The result showed there is differences on pain level before and after in giving red ginger compression with p value 0,000<a-0,05.